2016
DOI: 10.1161/circgenetics.116.001545
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Familial Hypercholesterolemia in Spain

Abstract: Recent genetic studies of FH highlight the great variability of the clinical phenotypes in HoFH and heterozygous FH (HeFH), the poor genotype-phenotype correlation, and the large clinical overlap between HoFH and HeFH. 15,[18][19][20] These findings can be explained based on the variations in the number of genes involved, the specific pathogenic mutations, and Background-Homozygous familial hypercholesterolemia (HoFH) is a rare disease characterized by elevated plasma levels of low-density lipoprotein choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 44 publications
2
22
1
Order By: Relevance
“…However, since the presence of still undiagnosed HoFH cannot be excluded, the frequency could be even higher. This frequency is similar to that estimated in the Netherlands [35], whereas it is higher than the Spanish prevalence [37]. The screening of the APOB and PCSK9 genes in our population would have probably identified additional HoFH patients, further increasing the disease prevalence.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, since the presence of still undiagnosed HoFH cannot be excluded, the frequency could be even higher. This frequency is similar to that estimated in the Netherlands [35], whereas it is higher than the Spanish prevalence [37]. The screening of the APOB and PCSK9 genes in our population would have probably identified additional HoFH patients, further increasing the disease prevalence.…”
Section: Discussionsupporting
confidence: 87%
“…This difference becomes even more evident after therapy with statin, ezetimibe, and anti-PCSK9 antibodies. Similar data were also reported for a Spanish population of HoFH patients [37]. From this perspective, genetic screening could allow for a better characterization of the response to PCSK9 inhibitors in HoFH, although larger studies are required.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“… 1 A recent study in Spain has revealed a prevalence of one case in 450 000 individuals, which is higher than previously expected. 2 Lifelong exposure to elevated LDL-C values greatly increases the risk of atherosclerotic cardiovascular disease (ASCVD) and premature death; untreated HoFH patients often do not survive past the age of 30 years. 3 In order to reduce the risk of ASCVD in patients with HoFH, it is important to correctly diagnose patients as early as possible and provide aggressive interventions to reduce the cumulative LDL-C burden.…”
Section: Introductionmentioning
confidence: 99%
“…Recent genetic studies of HoFH have highlighted the great variability of clinical phenotypes. 2 , 6 Indeed, HoFH is either caused by homozygosity or compound heterozygosity for mutations in the three major genes for LDL receptors, apolipoprotein B, and proprotein convertase subtilisin–kexin type 9 (PCSK9). The genetic heterogeneity in HoFH underlies the phenotypic variability.…”
Section: Discussionmentioning
confidence: 99%